2021
DOI: 10.1371/journal.ppat.1009510
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the Caenorhabditis elegans gut with human enteric bacterial pathogens leads to proteostasis disruption that is rescued by butyrate

Abstract: Protein conformational diseases are characterized by misfolding and toxic aggregation of metastable proteins, often culminating in neurodegeneration. Enteric bacteria influence the pathogenesis of neurodegenerative diseases; however, the complexity of the human microbiome hinders our understanding of how individual microbes influence these diseases. Disruption of host protein homeostasis, or proteostasis, affects the onset and progression of these diseases. To investigate the effect of bacteria on host proteos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 89 publications
(127 reference statements)
1
47
0
Order By: Relevance
“…Lipid analysis in fat-1-de cient nematodes revealed a signi cant reduction in heptadecaenoic acid, while other major FAs were unaffected 41 . Caenorhabditis elegans intestinal colonization causes protein homeostasis disruption, which can be improved by butyrate 42 . Two peptides, ACAN1 and NAK1, derived from the nematode phylum, have immunomodulatory functions and can inhibit the proliferation of CD4+ T cells and the production of IL-2 and TNF 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipid analysis in fat-1-de cient nematodes revealed a signi cant reduction in heptadecaenoic acid, while other major FAs were unaffected 41 . Caenorhabditis elegans intestinal colonization causes protein homeostasis disruption, which can be improved by butyrate 42 . Two peptides, ACAN1 and NAK1, derived from the nematode phylum, have immunomodulatory functions and can inhibit the proliferation of CD4+ T cells and the production of IL-2 and TNF 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, and after the extensive research work carried out to develop this work, future lines of research should focus on three main axes. First, new AChEI that delay the evolution of the disease, more efficient treatments are in progress based on super-AChEI designed under the “multitarget small molecule” umbrella [ 62 ]; secondly, studying epigenetics and designing drugs that are capable of modifying the human genome that cause AD [ 63 , 64 ] and, thirdly, the study of the human microbiota and how it influences the development of pathologies that trigger AD [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…To study the link between gut microbes and protein aggregation, Caenorhabditis elegans is used as a model organism. A study demonstrates that colonization of C. elegans gut with bacterial pathogens disrupted the intestines, muscles, and neurons and increased protein aggregation (Lau et al, 2021;Walker et al, 2021). Further investigation revealed that co-colonization with butyrogenic bacteria inhibited the aggregation of protein in C. elegans indicating that enteric bacteria play a role in the pathogenesis of neurodegenerative diseases such as Alzheimer's disease (Lau et al, 2021;Walker et al, 2021).…”
Section: Microbiome Role In Alzheimer and Dementiamentioning
confidence: 99%